'Bridging discourses' in a bilingual South African mathematics classroom with a collaborative teaching model - Tyler, Robyn (School of Education, 2015)
The majority of South Africa's learners have to access a curriculum in a language which is not their home language. Research has been conducted into several aspects of the challenge that this poses to educators and learners alike and how classroom discourse reflects this reality. This case study of a rural, bilingual Mathematics classroom in a holiday programme run by an NGO focuses on classroom talk to identify bridging discourses (Gibbons, 2006) used by the teacher, learning facilitator and learners. These bridging discourses serve to draw together the 'everyday' language of the learners and the subject-specific language of school Mathematics as well as to mediate between the culturally and linguistically disparate learners and teacher. I draw on a sociocultural view of learning, in particular the notion of mediation (Vygotsky, 1978), to frame this study. Classroom talk is conceptualised as a means of jointly constructing meaning (Mercer, 1995) which is framed by different discursive practices in different cultural settings (Gee, 1999; Alexander, 2001). Hence my research question is: within the particular discursive space of this classroom, how is mathematical meaning mediated through 'bridging discourses'?